2013
DOI: 10.1182/blood-2013-04-495804
|View full text |Cite
|
Sign up to set email alerts
|

A capture-sequencing strategy identifies IRF8, EBF1, and APRIL as novel IGH fusion partners in B-cell lymphoma

Abstract: • Targeted capture/nextgeneration sequencing is a powerful tool for the diagnosis of known and discovery of new IGH fusions in DLBCL.• IGH-mediated deregulation of IRF8 and EBF1 in DLBCL is characterized by induction of AID and BCL6, suppression of PRDM1, and antiapoptosis.The characterization of immunoglobulin heavy chain (IGH) translocations provides information on the diagnosis and guides therapeutic decisions in mature B-cell malignancies while enhancing our understanding of normal and malignant B-cell bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 39 publications
3
49
0
Order By: Relevance
“…Protein isolation, electrophoresis, and transfer to polyvinylidene difluoride (PVDF) membranes were performed as we previously described (24). Filters were immunoblotted with antibodies against p53 (sc-6243; Santa Cruz Biotechnology), phospho-p53 (Ser15, 9284; Cell Signaling Technology), p21 (F-5, sc-6246; Santa Cruz Biotechnology), phospho-STAT5-Tyr694 (4322; Cell Signaling Technology), Aicda (4975; Cell Signaling Technology), Socs1 (3950; Cell Signaling Technology), and ␤-actin (Sigma).…”
Section: Methodsmentioning
confidence: 99%
“…Protein isolation, electrophoresis, and transfer to polyvinylidene difluoride (PVDF) membranes were performed as we previously described (24). Filters were immunoblotted with antibodies against p53 (sc-6243; Santa Cruz Biotechnology), phospho-p53 (Ser15, 9284; Cell Signaling Technology), p21 (F-5, sc-6246; Santa Cruz Biotechnology), phospho-STAT5-Tyr694 (4322; Cell Signaling Technology), Aicda (4975; Cell Signaling Technology), Socs1 (3950; Cell Signaling Technology), and ␤-actin (Sigma).…”
Section: Methodsmentioning
confidence: 99%
“…Capture sequencing using frozen or formalinfixed paraffin-embedded tissue (FFPET) has proven sensitive for resolving single base-pair somatic mutations and SRs in multiple tumor types. [10][11][12][13][14] However, this approach remains unexplored for large-scale SR detection in lymphoma FFPET. Here, we report specific breakpoint anatomy for 36 novel PDL SRs, including 19 previously undescribed translocations and 17 intrachromosomal SRs.…”
Section: Introductionmentioning
confidence: 99%
“…IRF8 has also been implicated in the development of B cell-driven systemic autoimmune diseases in humans and mice (31,32). Finally, several recent studies have identified roles for IRF8 in the pathogenesis of human diffuse large B cell lymphoma (33,34) and probably mouse diffuse large B cell lymphoma as well (15).…”
Section: Discussionmentioning
confidence: 99%